1995
DOI: 10.1007/bf01540456
|View full text |Cite
|
Sign up to set email alerts
|

IR and turbidity studies of vitamin E-cholesterol-phospholipid membrane interactions

Abstract: Binary and tertiary mixture of alpha-tocophenol, cholesterol and dimyristoylphosphatidylcholine in the form of multilamellar liposomes were investigated by Fourier Transform Infrared and visible spectroscopy. Results of the FTIR and turbidity experiments indicate that alpha T decreases or diminishes the effect of cholesterol on the frequency and the bandwidth of the C-H stretching, CH2 scissoring and C = O stretching bands in FTIR spectra and the turbidity measurements (recorded as absorbance values at 440 nm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
(21 reference statements)
3
22
0
Order By: Relevance
“…Observing no effect for 6 mol% CLX in the liquid crystalline phase may have resulted from the effect of cholesterol on the membrane system. It has been widely accepted and also observed in our studies (data not shown) that cholesterol exerts opposite effects on the acyl chain conformation below and over the T m of phospholipids; disordering the membrane in the gel phase and ordering it in the liquid crystalline phase [1,24,31,33]. When the ternary system of DSPC:Chol:CLX is considered, the ordering effect of cholesterol in the liquid crystalline phase most probably have surpassed the similar effect of 6 mol% CLX resulting in no significant difference.…”
Section: Resultssupporting
confidence: 70%
“…Observing no effect for 6 mol% CLX in the liquid crystalline phase may have resulted from the effect of cholesterol on the membrane system. It has been widely accepted and also observed in our studies (data not shown) that cholesterol exerts opposite effects on the acyl chain conformation below and over the T m of phospholipids; disordering the membrane in the gel phase and ordering it in the liquid crystalline phase [1,24,31,33]. When the ternary system of DSPC:Chol:CLX is considered, the ordering effect of cholesterol in the liquid crystalline phase most probably have surpassed the similar effect of 6 mol% CLX resulting in no significant difference.…”
Section: Resultssupporting
confidence: 70%
“…The bandwidth jumps near the main phase transition. These modifications are analyzed in the literature [7,[11][12][13][14][15][16] for various types of phospholipids. We give a physical explanation of these modifications by analyzing the bandwidth values at different temperatures and different GS concentrations relevant for the dynamics of the chemical bonds implied in the IR bands' appearance.…”
Section: Resultsmentioning
confidence: 99%
“…Multilamellar DPPG liposomes were obtained [11,14,15] by vortexing DPPG thin films in excess Na 2 HPO 4 buffer for 20 min at 66 C. The liposomes were incubated in a shaking water bath for 1 h at a temperature around 45 C. The DPPG=GS systems were obtained from a stock solution of GS in ethanol. Multilamellar GS-containing vesicles were obtained using the same procedure followed for the DPPG vesicle preparation proposed in Refs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations